Calcium signaling during the plant-plant interaction of parasitic Cuscuta reflexa with its hosts - Albert, Markus; Kaiser, Bettina; van der Krol, Sander; Kaldenhoff, Ralf (Plant Signaling & Behavior, 2010)
The plant parasite Cuscuta reflexa induces various responses in compatible and incompatible host plants. The visual reactions of both types of host plants including obvious morphological changes require the recognition of Cuscuta ssp. A consequently initiated signaling cascade is triggered which leads to a tolerance of the infection or, in the case of some incompatible host plants, to resistance. Calcium (Ca 2+) release is the major second messenger during signal transduction. Therefore, we have studied Ca 2+ spiking in tomato and tobacco during infection with C. reflexa. In our recently published study1 Ca 2+ signals were monitored as bioluminescence in aequorin-expressing tomato plants after the onset of C. reflexa infestation. Signals at the attachment sites were observed from 30 to 48 h after infection. In an assay with leaf disks of aequorin-expressing tomato which were treated with different C. reflexa plant extracts it turned out that the substance that induced Ca 2+ release in the host plant was closely linked to the parasite's haustoria. © 2010 Landes Bioscience.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Calcium signaling; Cuscuta; Dodder; Plant parasitism